Impact of Multiprofessional Rounds on Critical Care Outcomes in the Surgical Trauma Intensive Care Unit. Issue 1 (January 2019) - Nahouraii, Michael R.; Karvetski, Colleen H.; Brintzenhoff, Rita A.; Sachdev, Gaurav; Evans, Susan L.; Huynh, Toan T.
Multiprofessional rounds (MPR) represent a mechanism for the coordination of care in critically ill patients. Herein, we examined the impact of MPR on ventilator days (Vent-day), ICU length of stay (LOS), hospital LOS (HLOS), and mortality. A team developed guidelines for MPR, which began in February 2016. Patients admitted between November 2015 and March 2017 with Acute Physiology and Chronic Health Evaluation (APACHE) IV and injury severity scores were included. Outcome data consisted of Vent-day, Vent-day observed/expected ratio (O/E), ICU LOS, ICU LOS O/E, HLOS, HLOS-O/E, and mortality. Linear regression models are constructed to assess statistical significance. A total of 3372 patients were included. Among surgical patients (n = 343 pre-MPR, n = 1675 post-MPR), MPR was associated with decreases in Vent-day O/E (0.74 pre, 0.59 post, P = 0.03), ICU LOS O/E (0.67 pre, 0.61 post, P = 0.01), and HLOS-O/E (1.47 pre, 1.22 post, P = 0.0005). No mortality difference was observed. For trauma patients (n = 221 pre, n = 1133 post), MPR resulted in a reduction in Vent-days (2.2 days pre, 1.6 days post, P = 0.05). However, no differences were observed for Vent-day O/E, ICU LOS O/E, HLOS-O/E, and mortality. Implementation of MPR was associated with improved outcomes for surgical trauma ICU patients. Sustainability of MPR remains a challenge and requires education and engagement.